2021
DOI: 10.1016/j.sjbs.2020.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Public and healthcare providers awareness of Coronavirus (COVID-19) in Qassim Region, Saudi Arabia

Abstract: Background The rapid and extensive spread of the COVID-19 pandemic has become a major cause of concern for both general public and healthcare profession. Objective The aim of this study is to analyze and evaluate the awareness of both the general public and healthcare providers in Qassim region in Saudi Arabia. Method A cross-sectional study was conducted randomly in different shopping malls in Qassim region from 10th of February to 10th of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
5
11
0
Order By: Relevance
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%
“…Awareness campaigns are recommended to improve any misbeliefs and/or risky behaviors. Al-Rasheedi/Jan 2021 43 Public and healthcare providers awareness of Coronavirus (COVID-19) in Qassim Region, Saudi Arabia 130 participants from shopping malls In-person using a structured questionnaire General public/HCPs from Qassim Region showed adequate awareness of COVID-19. Implementing periodic educational interventions and training programs on infection control practices for COVID-19 across all healthcare professions is highly recommended.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…This high level of awareness reflects the success of the health campaigns led by the MOH, which used several approaches to reach people, including social platforms, daily updated statistics, health apps and educational webpages. Participants in this study show better awareness about COVID-19 compared to those analyzed in other studies, including in Riyadh, 21 Qassim 32 and other Saudi cities. 33 …”
Section: Discussionmentioning
confidence: 38%
“…Furthermore, Tawakkalna, a mobile application, was developed by the Ministry of Health and the Ministry of the Interior, to allow people to meet their needs and plan their journeys during the curfew period. [37]…”
Section: Transmissionmentioning
confidence: 99%